Development and initial evaluation of the COnfident Parent INternet Guide program for parents of 3–8 year olds - Hutchings, Judy; Owen, Dawn A.; Williams, Margiad E. (Frontiers in Psychology, 2023)
Introduction Positive parenting promotes children’s cognitive, social and emotional development and parenting programs based on social learning theory are effective in supporting parents to help reduce behavioral problems among high challenge children. However there is less evidence for programs with non-clinical populations. COPING (COnfident Parent INternet Guide) is a 10-week online universal program for parents of 3 – 8 year olds presenting evidence-informed principles based on social learning theory to support parents in addressing common challenges with their children. This study explored the development and feasibility of delivery of the program in terms of recruitment, retention and acceptability. It also reports on initial program effectiveness, evaluated via a pilot randomized controlled trial. Methods Data on child behavior, parental skills and mental health were collected at baseline and three months later for all participants and six months post-baseline for the intervention group only. Results Those parents who accessed the course provided very positive feedback however the trial experienced challenges with recruitment and initial engagement, particularly for parents referred by professionals. For parents who engaged with the program there were significant improvements in reported parenting skills with evidence of longer-term maintenance. Discussion This paper provides limited evidence of effectiveness for the COPING program however further feasibility work, particularly around recruitment, is needed before conducting larger effectiveness trials.